Peningkatan Loyalitas Pelanggan Melalui E-CRM Pada Doktorandus Koffie - Taqwa Putra Budi Purnomo Sidi; Justin Bongsoikrama; Triana Anggraini; Devit Setiono (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to investigate whether E-CRM can moderate the quality of products on customer loyalty. The sample consisted of 100 respondents from the academic community of Universitas Budi Luhur in 2023. Data were collected directly through Google Forms, and data analysis was conducted using SEM-PLS with outer and inner model stages. The research results indicate that the quality of products significantly influences customer loyalty with a significance value of 0.018. E-CRM also significantly affects customer loyalty with a significance value of 0.000. However, E-CRM does not moderate the relationship between product quality and customer loyalty, with a significance value of 0.707